1994
DOI: 10.1254/jjp.66.173
|View full text |Cite
|
Sign up to set email alerts
|

Possible Participation of Histamine H3-Receptors in the Regulation of Anaphylactic Histamine Release from Isolated Rat Peritoneal Mast Cells

Abstract: ABSTRACT-Anaphylactic histamine release from isolated rat peritoneal mast cells was concentration dependently blocked by a 5-min treatment with exogenous histamine at 0.9 and 9 pM and enhanced by a 20 to 30-min treatment with thioperamide (H3-antagonist) at 3 pM with significance, but little affected by mepyramine (H,-antagonist) and cimetidine (H2-antagonist) at the cell concentration of 106 mast cells/ml. At a low concentration of mast cells (104 mast cells/ml), (R)-a-methylhistamine (a-MH), an H3-agonist, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In 1992, Mackay and Pearce reported that anti-IgE-and ConA-induced histamine release was reduced after mast cell purification [19]. Furthermore, Kohno et al confirmed that antigeninduced histamine release was also reduced after purification [20]. These results clearly indicate that purificationassociated reduction of histamine release is a specific phenomenon for IgE-dependent mast cell activation.…”
Section: Discussionmentioning
confidence: 95%
“…In 1992, Mackay and Pearce reported that anti-IgE-and ConA-induced histamine release was reduced after mast cell purification [19]. Furthermore, Kohno et al confirmed that antigeninduced histamine release was also reduced after purification [20]. These results clearly indicate that purificationassociated reduction of histamine release is a specific phenomenon for IgE-dependent mast cell activation.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature, it has been unclear whether mast cells express the H 3 receptor. Most studies used thioperamide as a specific H 3 antagonist (Kohno et al, 1994;Bissonnette, 1996), but recent data indicate that both the mouse and human H 4 receptor can bind thioperamide as well (Liu et al, 2001b). It is therefore likely that the effects of histamine on mast cells that can be blocked by thioperamide are actually mediated by H 4 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Purified peritoneal mast cells of rats usually release a small amount of histamine upon IgE-dependent stimulation, [19][20][21][22][23] therefore, investigators have sometimes employed phosphatidylserine to potentiate the response. [28][29][30] Previously, we demonstrated that the low IgE-dependent histamine release from purified mast cells could be recovered or potentiated by reconstitution with separated non-mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Contact of mast cells with purification media does not result in the reduced histamine release, but the purification itself is crucial. Furthermore, the reduction of histamine release from purified mast cells seems to be a specific phenomenon for IgE-dependent mast cell activation, and the reduced histamine release is recovered by reconstituting with non-mast cells separated from mast cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation